Evaluación de las actividades del buceo recreativo sobre la estructura comunitaria de algunos arrecifes del Parque Nacional Archipiélago de Los Roques, Venezuela - Zubillaga, Ainhoa L. (2003)
In order to evaluate if snorkeling had significant effects on coral community structure, three different coral reefs (Madrizquí, Pelona de Rabusquí and Crasquí) located at Archipelago Los Roques National Park, Venezuela, were surveyed. For each site, the coral community structure of two different areas, one subjected to intense snorkeling use (FB) and other not frequently used (PFB), were compared. Community structure was determined with 1 m2quadrants and 20 m-long transects. These communities were described in terms of species richness, diversity (Shannon–Wiener) and evenness indexes, live and dead coral cover and cover of other organisms (sponges, octocorals and algae). Comparisons within sites were performed with a Kruskall – Wallis test. A total of 24 species of scleractinian corals were found. Live coral cover ranged from 29.9% ± 26.43 (Crasquí) to 34.55% ± 6.43 (Madrizquí), while dead coral cover ranged from 32.51% ± 2.86 (Madrizquí) to 60.78% ± 21.3 (Pelona de Rabusquí). The PFB areas showed higher live coral cover compared to FB areas; however, significant differences were only found in Crasquí and Pelona de Rabusquí (p < 0.05). Species richness, diversity and evenness were variable and no trends were observed between FB and PFB areas. The frequency of both damaged and diseased colonies were low (< 1%), most damages observed were natural (parrotfish predation). Damages caused by divers such as fin impacts, were not found at the reefs studied. These results suggest that, currently, diving pressure is not as high to cause massive loses of live coral cover in these reefs. However, the lack of strict controls for these activities might produce long-term changes in the structure of these coral communities.